De Gaulle and the ordinance of 07 March 1944, Historical context and dimensions - cheboub , Mohammed (The Algerian Historical Journal, 2026)
The follower of France's location during the fronts of World War II finds that it was defeated and in the early years of the outbreak of that war, and then that early defeat has been reflected on its colonies, which were seeking liberation, we mention Algeria, which tried the leaders of the national movement at the time to continue the struggle, where Farhat Abbas issued a statement in February 1943, which included many and varied demands, the most important of which is the denunciation of colonialism and its forms, that statement, although it came in the circumstances of the war, but it was resonated and even reached Allied officials in Algeria